Electron transport through ac driven graphene p–n junctions - Zhang, Zhi-Qiang; Kang, Yan-Zhuo; Ding, Kai-He (Physics letters. A, 2018)
We study the electronic transport through ac driven graphene p–n junctions under a perpendicular magnetic field. It is found that subject to the transversely or longitudinally polarized ac field, in the p–n region, the conductance versus the on-site energy of the right electrode exhibits a characteristic structure with a zero value plateau and the followed oscillation peaks, whose widths are greatly suppressed by the ac field. In the n–n region, the conductance plateaus at G=(n+1/2)(4e2/h) (n is an integer) shrink for the transversely polarized ac field, whereas accompanied with the addition of the new quantized plateaus at G=n(4e2/h) for the longitudinally polarized ac field. The combined influence of the ac field with the disorder can trigger a change in the mixing of the hole and electron states at the p–n interface, which leads to a destruction of the plateaus structure in the conductance versus the disorder strength with the emergence of new ones. The influence of the elliptically and circularly polarized ac field on the conductance is also shown. •We study the electronic transport through ac driven graphene p–n junctions under a perpendicular magnetic field.•In the p–n region, the widths of the conductance oscillation peaks are suppressed by the ac field.•In the n–n region, the new conductance plateaus appear for the longitudinally polarized ac field.•The combined influence of the ac field with the disorder can lead to a destruction of the conductance plateaus.